APPLICATION OF ZINC FERRITE SILICA GEL COMPOSITE PHOTOCATALYSTS FOR THE TREATMENT OF TEXTILE EFFLUENTS - PAUL E. D; IBRAHIM, D; YASHIM Z. I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
The photocatalytic activity of the zinc ferrite silica gel composite photocatalysts was evaluated using decolourization of Methylene Blue (MB) which revealed that 30 wt% ZnFe2O4/SiO2 was found to have the best photocatalytic activity than 10 wt%, 20 wt% while 40 wt% showed significant reduction in the photocatalytic activity which can be attributed to the increased agglomeration of the zinc particle on silica gel, thereby decreasing the rate of diffusion of photogenerated electron-hole pairs on the MB molecule at the interface of solid photocatalysts and the MB solution. The SiO2 support improves the photocalytic activity of the ZnFe2O4 under visible irradiation. The application of the best zinc ferrite silica gel composite photocatalysts to the treatment of real textile effluent resulted more efficiency in the reduction of the effluent’s color, COD, BOD than the bare zinc ferrite and the photolysis. 50% color removal, 46% COD and 45% BOD with 30 wt% ZnFe2O4/SiO2 while 30% Color removal, 25% COD and 24% BOD with bare ZnFe2O4 and 14% color removal, 10% COD, 10% BOD using photolysis.